Mobile middleware platform for secure vessel traffic system in IoT service environment. Issue 6 (10th November 2014) - Park, Namje; Bang, Hyo‐Chan
Abstract: The Inter‐VTS Data Exchange Format (IVEF) service is the draft standard designed for exchange of information on sea traffic between the vessel traffic systems and between the vessels. Standardization of this service is under way as a part of the next‐generation navigation system, called e‐Navigation. The International Association of Lighthouse Authorities suggests, on its recommendation V‐145, the IVEF service model and the protocol for provisioning of this service. But the detailed configuration of this service must be designed by the users. IVEF service is aimed at establishing a common framework to ensure exchange of ship information between vessel traffic service (VTS) centers gained via automatic ship identification device, closed‐circuit television, radar system and other devices. Robust exchange of marine traffic information between VTS centers through IVEF service will enable related authorities to identify location of domestic and international ships in the coastal waters real‐time and predict expected sea route, thus ensure effective sea route control and pre‐emptive response to potential disasters or accidents. This paper suggests, based on the basic service model and protocol provided in the recommendation V‐145, the implementation of the Jeju‐VTS middleware, which will facilitate exchange of information on sea traffic. This paper developed a system enabling IVEF service simulation under an Internet of Things environment made possible by improving IVEF software development kit, which is an open source. For this, a mobile phone loaded with Android platform and desk top PC has been used for emulation of a ship on voyage and VTS center. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : This paper suggests, based on the basic service model and protocol provided in the recommendation V‐145, the implementation of the Jeju‐VTS middleware will facilitate exchange of information on sea traffic. This paper developed a system enabling IVEF service simulation under an Internet of Things environment made possible by improving IVEF software development kit, which is an open source.